Nutrition-sensitive value chains: A guide for project design. Volumes II: Resources - Peña, Isabel de la; Garrett, James (International Fund for Agricultural Development, 2018)
Volume II provides tips and a collection of sample resources needed to conduct the diagnostic studies (Steps 1 to 4) described in Volume I. Specifically, Volume II provides sample terms of reference for each step, tables with a summary of research questions and data collection methods/tools, as well as specific tools and templates for data collection.